(3GdJNWjW GdGSJQGJjLj (B:s (3YQV fXQj hJWHjbj (B/s - (3GdcQNj, eLjOs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2009)
(3eONd aj GdJNWjW,eONd aj GdJNWjW GdGSJQGJjLj,QDjI hQSGdI hbje GdefXeI hTYGQ GdefXeI,JMdjd HjFI GdefXeI hGdaLhGJ,GdbVGjG GdCSGSjI ddefXeI,GdCgOGa GdGSJQGJjLjI hGdaQYjI,GdNWI GdJfajPjI GdeJGHYI hGdJbjje,fLGM haTd GdJNWjW GdESJQGJjLj,HfGA GdNWI GdGSJQGJjLjI NWhI NWhIs
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdJfXjes